Determination of antimicrobial activity by defence fluid of Macrotermes Carbonarius on selected soil microbes - Priyono, Ameera Nur Afiqah (2020)
Macrotermes carbonarius soldiers are able to deliver painful bites using their large mandibles and secrete the defence fluid when sensing danger environment. From previous studies, the soldier of various termite species produce potent defensive secretions that can have antifungal and antibacterial properties but little is known about their effectiveness to fight against various types of microbe found colonizing in their mound. In addition, there is no previous study done on the interaction of defence fluid of M. carbonarius and their soil microbes. This study explored the antimicrobial activity of defence fluid of M. carbonarius against selected soil microbes using Kirby Bauer Test Disk Diffusion and its Minimum inhibitory concentration (MIC) were analyzed by using Tukey post hoc test ANOVA. Four different concentration of defence fluid crude extract (0.5mg/ml, 1.0mg/ml, 5.0mg/ml and 10.0mg/ml) were used and based on the result obtained, the crude extract successfully showed its MIC against Unknown Bacteria 001 and Unknown Bacteria 002 at concentration of 5.0mg/ml and 0.5 mg/ml respectively. Both Unknown Bacteria 001 and Unknown Bacteria 002 shows the diameter of inhibition zone with overall mean and standard deviation of 7.00 ± 1.128mm and 7.50 ± 0.674mm respectively. These findings, together with the present results indicate that antimicrobial properties of termite defence fluid could be used as a source of natural products providing a new solution against the problem of bacterial resistance to antibiotics and used as a reference for any further research on defence fluid of termites.